KORELASI KONDISI KESEHATAN, TINGKAT NYERI, GAYA HIDUP DAN PENGETAHUAN DENGAN MOBILISASI DINI PADA PASIEN POST OP FRAKTUR EKSTREMITAS BAWAH - Ritawati Ritawati; Nurleli Nurleli; T. Iskandar Faisal; Reska Asnita; Nuswatul Khaira (Poltekkes Kemenkes Aceh, 2023)
As many as 6 million people are injured in traffic accidents every year. Fractures are one of the most common injuries experienced by victims with a prevalence of 5.5%, and the body parts most affected by fractures are the lower extremities (67%). Early mobilization is one of the interventions for postoperative recovery in patients so that the rehabilitation process takes place quickly. Many factors influence the implementation of early mobilization. The purpose of this study was to determine what factors were associated with early mobilization in postoperative patients with lower limb fractures at Meuraxa Hospital in Banda Aceh. The design of this study used an analytic observational method with a cross sectional approach. The population in this study were all postoperative patients with lower limb fractures in the male and female surgical inpatient rooms at Meuraxa Hospital, Banda Aceh. Sampling using purposive sampling technique with a total sample of 36 people. The univariate and bivariate data analysis used the Chi Square statistical test. The results of the study showed that there was a relationship between health condition factors, namely hemoglobin (p=0.045), pain level (p=0.006), lifestyle factors (p=0.002), and knowledge factors (p=0.001) with early mobilization in postnatal patients. Lower Extremity Fracture surgery.